La Reforma luterana y los orígenes de la democracia representativa - Ramón Jacobo, Gustavo (2018)
Under the initial warning that neither Luther was a democrat nor the Protestant Reformation had among its aims the political democratization of society, this article explores three dimensions of movement and thought of its main referent, which are at the base of the emergence of representative democracies: its media, technology and communication dimension; its geopolitical and economic dimension and its ideological dimension. In Luther and the Reformation the tensions of a change of epoch of which they are a product are appreciated, but at the same time they embody it in a religious phenomenon and from that same perspective they propel it.